Efeitos da ventilação não invasiva de alta frequência em recém-nascidos prematuros: protocolo de revisão sistemática - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Introduction: Prematurity has been the main cause of neonatal mortality in the world for at least a decade, and it is a condition that can be induced by several factors. High Frequency non-invasive ventilation is a promising new mode of non-invasive ventilation that aims to offer adequate ventilation and oxygenation, but much has yet been discussed about its effectiveness and safety. Objective: To evaluate the effectiveness and safety of noninvasive high-frequency oscillatory, jet, and percussive ventilation in premature infants. Methods: To this end, we will carry out a systematic review. The study protocol was recorded on the Prosperous Platform. We will include premature newborns who used high-frequency non-invasive ventilation requiring ventilation as an initial support, after extubation or as a rescue mode (after failure of initial non-invasive therapy). The searches will be carried out in the databases: Medical Literature Analysis and Retrieval System Online (MEDLINE) via Pubmed, Excerpta Medica dataBASE (Embase) via Elsevier, Cochrane Central Register of Controlled Trials (CENTRAL) via Cochrane Library, Latin American and Caribbean Literature in Health Sciences (LILACS) via the Virtual Health Library Portal and Physiotherapy Evidence Database We will evaluate the methodological rigor of the included studies and the certainty of the evidence of the main outcomes of the systematic review using Cochrane's Risk of Bias 2.0 tool and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach, respectively. The selection of studies, data extraction, evaluation of the bias of the included studies and evaluation of the certainty of the evidence will be carried out by two independent researchers. Expected Results: The results of this review are expected to present a critical and up-to-date summary of the topic and facilitate safer decision-making by physiotherapists regarding the best recommendation for ventilatory support in the NICU, based on the best scientific evidence currently available.
Keywords: Nascimento prematuro; Recém-nascido prematuro; Ventilação não invasiva; Ventilação de alta frequência; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; ODS 3 – Saúde e bem-estar